Precision criteria to derive sample size when designing pediatric pharmacokinetic studies: Which measure of variability should be used?. (19th November 2013) - Salem, Farzaneh; Ogungbenro, Kayode; Vajjah, Pavan; Johnson, Trevor N.; Aarons, Leon; Rostami‐Hodjegan, Amin
Abstract A new approach for calculation of sample size in pediatric clinical pharmacokinetic studies was suggested based on desired precision for a pharmacokinetic parameter of interest. The estimate of variability for sample size calculations could be obtained from different sources. It is not known whether these sources constantly show higher/lower variability across compounds and age groups. We obtained estimates of variability for clearance, volume of distribution and area under the plasma concentration‐time curve for 5 drugs from adult/pediatric classic clinical pharmacokinetic studies, and physiologically based pharmacokinetics (PBPK) combined with in vitro–in vivo extrapolation. Estimates were applied to the proposal methodology for non‐compartmental analysis. Sample size was different for each drug based on various estimates of variability from different pharmacokinetic parameters and depending on the age. Overall, there was no consistent discrepancy in sample size calculated according to the source of variability. A conservative approach should be taken when using "precision based methodology" knowing that various sources of initial estimates of variability will not lead to similar sample size calculations. Although PBPK simulations could be used for estimating variability, further work is required to investigate the best approach to estimate variability of pharmacokinetic parameters in pediatric populations and hence sample size calculations.